A comparison of emergency department medical records to parental self-reporting of traumatic brain injury symptoms. (6th April 2018) - McKinlay, Audrey; Lin, Alanah; Than, Martin
Aim: Studies have shown Emergency Department (ED) recording of traumatic brain injury (TBI) cases to be poor.Methods: Parents of children aged 2–12 who attended an ED with injury to the head completed a concussion checklist which was compared with medical records.Results: ED medical records commonly used head injury (HI), concussion, minor-HI and mild-HI without distinction between TBI and superficial HI. Recalled symptoms included vomiting, blurred vision and headaches versus headaches, fatigue and feeling sick from parents who reported more concussive symptoms. More cases of TBI were identifiable from parental recall compared with medical records, which recorded fewer symptoms for diagnosis, prognosis and statistical reporting of TBI.Conclusion: Clear guidelines need to be implemented to improve retrospective diagnosis for incidence gathering and future clinical use.